Developing 3D cadastre registration system - Ahmad Nasruddin, Mohd. Hasif; Hassan, Muhammad Imzan; Abdul Rahman, Alias (2008)
The establishment of Malaysia cadastral system is to monitor matters of land especially the land ownership. The system is setup to ensure consistency in cadastral information that comes from cadastral survey and cadastral land registration. In general, the cadastral survey and cadastral land registration are managed by Department of Survey and Mapping Malaysia (DSMM) and Land Offices (LO) respectively. The cadastral object can be either a complete land parcel, parcel of storey houses (strata) e.g. apartments, flats residential or parcel below the surface (stratum). There is a need for 3D cadastre registration as real-estate property is actually in 3D. Therefore, the new cadastral system should reflect the existence of the real-world objects - 3D physical objects and have its own legal rights. Current 3D computing technology could be used to develop a registration system for 3D Cadastre and eventually a solution for 3D Cadastre objects situations. One of the main challenges is to transform the proposed cadastre model into computer environment i.e. logical model. The validation of logical model will be then encoded in the spatial database. Spatial DBMS is the foundation for both GIS (presentation, analysis) and CAD (creating the 3D models). It offers spatial data type in its data model structure and also in the query language and it can interact with the spatial DBMS. The cadastre objects will be also link with the land registration attributes. This paper discusses a development of 3D registration system for cadastre objects in 3D. The paper elaborates on the integration of Oracle Spatial and Autodesk Map 3D towards developing a 3D Cadastre registration system